Medical Device Integration with Electronic Health Records: A Case Study of University of Nairobi Health Services, Kenya - Mugo, David Muchangi; Nzyoka, Benard Mutisya Nzyoka; Ng’ang’a , Stephen Mburu (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2020)
In this study, we describe a demonstration in which available electronic medical records system (EMR) was successfully integrated with a wireless blood pressure monitor (BPM). This was implemented by adopting the use of RESTful Application Programming Interface (API) technologies and commonly established standards designed for medical devices interoperability. Before deploying the prototype, we conducted pilot tests at the University of Nairobi, nursing station to get feedback on the time spent using the conventional blood pressure data capture methods and the newly integrated application. Clinical data from the device was exchanged adhering to the HL7/XML standard communication protocol. The findings indicate a positive outcome was availed on the time taken for the blood pressure readings, time spent by the patient at the nursing station, doctor’s time to search the patients’ blood pressure readings as well as the data accuracy fed in the EMR system.